RANCANG BANGUN GAME AUGMENTED REALITY BERBASIS ANDROID SEBAGAI PEMBELAJARAN KEDISIPLINAN ANAK INDONESIA - Wiranata, Ardi; Hutabri, Ellbert (Computer Science and Industrial Engineering, 2021)
Education nowdays become a hard material to teach to children aspecially discipline, but now with the help of technologies and augmented reality which is popular with the community, developer can make a game about discipline to let children and other have fun while studying and an extra augmented reality function. The method that are used in this development is the multimedia development life cycle (MDLC) which consist of 6 stage that namely concept, design, materials collecting, assembl, testing, and distribution. The result of this development were tested using alpha test. This study focused at junior high school stage as source of learning discipline at home, school, or public places are expected to increase students awareness of disciplined behavior.